(untitled) (Scientia Agropecuaria, 2025)
The phytopathogen M. roreri represents one of the main phytosanitary problems worldwide, it is still a challenge and represents a risk for almond production. The efficient use of fungicides reduces the impact on the environment and contributes to the care for the non-resistance of the pathogen. This work carried out an experimental study to estimate the capacity of chemical fungicides for in vitro and in vivo management of the disease and also analyzed the effective isolates of the pathogen that have been reported in laboratory conditions in Ecuador. Three experimental trials were carried out, the first with a DCA to estimate effective doses of azoxystrobin, copper sulfate pentahydrate and chlorothalonil under in vitro conditions; the second a factorial DCA to evaluate the effect of antifungals on loose fruits inoculated with the pathogen under controlled conditions using conidia spraying; and a DCL to study the effect of combined fungicides for pathogen decline under field conditions, the variables evaluated were: growth area, PIC in Petri boxes, incidence, external severity on cocoa fruits. Copper sulfate and azoxystrobin showed high efficacy in vitro against M. roreri, with control greater than 90%. In the field, fungicide combinations significantly reduced the incidence and severity of the pathogen in cocoa; loose cocoa pods were not suitable for evaluating virulence or antifungal efficacy. In the incidence analysis, 59.09% of M. roreri isolates at the in vitro level did not show significant genetic differences in Ecuador.